EFFECT OF NaCl STRESS AMELIORATED WITH CaCl2 ON NUCLEOTIDES AND POLYPEPTIDES DURING GERMINATION IN GROUNDNUT (ARACHIS HYPOGAEA L.) - S. K. M. BASHA; G. FAREEDA; N. SAVITHRAMMA (The Bioscan, 2010)
The present research work was carried out to elucidate the adverse effect of NaCl salinity and its amelioration by CaCl2 during early seedlings growth of two groundnut cultivars (cv, TPT-2 and cv. TCGS-29) CaCl2 treated seedlings showed higher levels of DNA and RNA contents when compared to all other treatments during seedlings growth. However, the DNA content was more in the cv. TCGS-29 on all the days after sowing. NaCl treatment caused decrease in the levels of lipoxygenase (LOX) activity when compared to the seedlings treated with either CaCl2 or its combination with NaCl. LOX showed a single peak with an UV absorption maximum at 235 nm on HPLC. Three major polypeptides (66kD, 47kD and 18.4 kD) appeared predominantly in control and treated seedlings of cotyledons in both varieties but they were absent in the embryonic axis. Cv. TPT-2 is stress tolerant than cv. TCG-29.30 mM and 15mM Ca2+ treatment alleviated the stress effect in cv, TPT-2 and TCGS-29 respectively.